LEGAL PROTECTION FOR CERTAIN TIME WORK AGREEMENT (PKWT) WORKERS WHO EXPERIENCE WORK ACCIDENTS - Tsabitah Siska Ardini; Al Qodar Purwo Sulistyo (Universitas Labuhanbatu, 2024)
Workers experience work accidents are protected by the state. Several legal protections regulate the protection of workers who experience work accidents. The research method that I use is the normative legal research method, namely research carried out by studying and reviewing material that discusses a legal issue. Normative juridical research method through a statutory approach. Law Number 13 of 2003 concerning Employment which regulates workers who experience work accidents. Law Number 24 of 2011 concerning the Social Security Administering Body. My aim in writing this journal is so that workers can more easily find out about the protection that workers receive. All workers with Certain Time Work Agreement (PKWT), permanent, casual daily workers, and outsourced workers should receive equal social, technical, economic, repressive, and preventive protection measures for workers affected by work accidents not registered with the Social Security Administrator (BPJS) program.Key words: work accidents; workers; employer; Employment agreement